Research on Legal Regulation of Infringement by Weak Artificial Intelligence Medical Robots - Min ZHAO; Yuxuan SHI (Yixue yu zhexue, 2025)
The rapid development of medical artificial intelligence (AI) has brought significant convenience to human beings, but it has also given rise to accompanying infringement. Due to the lag in legislation, the regulation of infringement caused by medical robots poses challenges that hinder the application of AI in the medical field. This paper analyzes the challenges in attributing infringement to weak AI medical robots and clarifies their legal subject status. Drawing on international experiences, it proposes regulatory recommendations such as establishing national standards for medical robots, defining types of product defects, expanding the scope of producers, and including certain infringements caused by intelligent medical robots under the framework of strict liability for ultrahazardous activities. These suggestions aim to support the responsible use, advancement, and development of AI technologies in the medical field.